The Effectiveness of Reading using the Fernald Method for Mentally Retarded Children - Putri, Brilliandani Kirara; Mastuti, Endah (Psikostudia : Jurnal Psikologi, 2025)
Reading is a very important skill to master. The ability to read is an important part of human life as a window of knowledge. But not all students can read and understand reading fluently. Especially mentally retarded students who have intellectual abilities, memory, and concentration are very limited. The purpose of this study was to see the effect of Fernald's method in learning to read children with mental retardation who have problems in reading. The subjects of this study were third grade elementary school students with mental retardation who had early reading problems. The research method is single subject experiment and analysis technique using pretest posttest score chart. The data collection instrument used is WISC. Fernald's method was given in 6 meeting Sessions. The results of the study showed an increase in reading ability after the intervention to the subjects. So it can be concluded that Fernald's method can improve reading skills in third grade students who are mentally retarded. Membaca merupakan keterampilan esensial yang berperan sebagai pintu gerbang pengetahuan. Namun, tidak semua peserta didik memiliki kapasitas yang sama dalam menguasainya, terutama siswa dengan retardasi mental yang mengalami keterbatasan dalam intelegensi, memori, dan konsentrasi. Penelitian ini bertujuan mengkaji efektivitas metode Fernald dalam pembelajaran membaca bagi siswa dengan hambatan intelektual. Subjek penelitian adalah siswa kelas tiga SD yang mengalami kesulitan dalam membaca awal. Menggunakan pendekatan eksperimen subjek tunggal dan analisis grafis melalui skor pretest dan posttest, data dikumpulkan dengan instrumen WISC. Hasil menunjukkan adanya peningkatan kompetensi membaca setelah enam sesi penerapan metode Fernald, yang menegaskan potensi metode ini dalam mendukung perkembangan literasi pada anak berkebutuhan khusus. Tes informal disusun berdasarkan kurikulum sekolah Abdurahman (2012).